Case study: Evaluation of the automation of material handling with mobile robots - Adriana F. Melo; Lindsay M. Corneal (International Journal of Quality Innovation, 2020)
The automation of material handling is one of the solutions that many companies are relying on to reach their goals related to productivity increment, floor space optimization, higher standards for factory's safety, and allocation of workers to valueadded activities. Therefore, the objective of this study was to evaluate the current state of the material flow of finished goods for an automotive parts supplier plant and the technology available on the market to verify if it was worthwhile to invest in material handling automation. The analysis included the use of discrete event simulation to evaluate the different layout approaches combined with the mobile robots' performance. It was proven that the tandem layout was the most beneficial approach to the analyzed plant's reality with a minimal of three robots. Improvements to the material flow and automation of the labeling process were also proposed based on the study.
Keywords: 650